Researching Violence against Women in Aotearoa/New Zealand - Mandy Morgan (Journal of Educational, Health and Community Psychology, 2014)
AbstractThis paper discusses strategies for research with women who have been victimised in their intimate relationships with their partners.Â  I will discuss the specific issues that concern the vulnerability of women victimised by intimate partner violence: experiences of intimate violence, stereotyping, minimisation, sexual violence, protection of children, the meaning of safety. Examples from the accounts of women who whose partners had been prosecuted for violence against them, and those who had sought legal interventions like protection orders, will illustrate how each of these issues needs to be taken into account when conducting research with abused women.Â  Strategies that we have used to deal with these issues in studies conducted in the Domestic Violence Interventions and Services Research Programme will be discussed, with illustrations of the complexities of putting them into practice.Keyword: domestic violence, intimate relationships, victimization, and New Zealand women